Physical oceanography during ALKOR cruise AL457 - Hans-Harald Hinrichsen; Burkhard von Dewitz; Andreas Lehmann (PANGAEA, 2025)
Conductivity-temperature-depth profiles were measured using a CTD during RV ALKOR cruise AL457. The CTD was equipped with duplicate sensors for temperature, conductivity and oxygen. All sensors are calibrated irregularly. Data were connected to the station book of the specific cruise as available in the DSHIP database.
In: Hinrichsen, Hans-Harald; Reusch, Thorsten B H; Dierking, Jan; Lehmann, Andreas (2025): Timeseries of physical oceanography in the Baltic Sea from 2011-2022 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.979407